Last minute policies and the incumbency advantage - Elena Manzoni; Stefan P. Penczynski (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper models a purely informational mechanism behind the incumbency advantage. In a two-period electoral campaign with two policy issues, a specialized incumbent and an unspecialized, but possibly more competent challenger compete for election by voters who are heterogeneously informed about the state of the world. Due to the asymmetries in government responsibility between candidates, the incumbent's statements may convey information on the relevance of the issues to voters. In equilibrium, the incumbent sometimes strategically releases his statement early and thus signals the importance of his signature issue to the voters. This gives rise to the incumbency advantage. We find that, since the incumbent's positioning on the issue reveals private information which the challenger can use in later statements, the incumbent's incentives to distort the campaign are decreasing in the quality of the incumbent, as previously documented by the empirical literature. However, we show that this implies a non-monotonicity in the distortions that arise in equilibrium.
Keywords: D72; D82; D60; 330; incumbency advantage; electoral competition; information revelation